HUBUNGAN KONFLIK ANTARWARGA DENGAN KEAMANAN KEMANUSIAAN DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (STUDI TAWURAN WARGA DI KECAMATAN JOHAR BARU JAKARTA PUSAT 2010-201) - _, Munawar (Jurnal Ketahanan Nasional, 2013)
This paper explained the residentsâ conflicts in Jakarta. The qualitative and quantitative data showed the significant relations of conflict, security and regional resilience. Therefore to eliminated the conflicts, the taken strategy was creating employment, enhancing education level, enhancing the community life and enhancing the social control function role which embodied in security forces assertiveness in conflict resolution including intelligence forcesâ early preventing.Keywords: Residentsâ Conflict, Human Security, and Regional Resilience.